PEMBUATAN KERAMBA FLOATING CAGE PADA DAERAH RAWAN BANJIR ROB DI PESISIR PEKALONGAN - Heri Ariadi; M. Bahrus Syakirin (LPPM Universitas Pekalongan, 2021)
Floating net cages are models of aquaculture cages for fish cultivation that are adaptable to the phenomenon of flooding and tidal waves. The purpose of this social service is to create a model of floating cages that can be used as a pond for fish cultivation in areas prone to tidal flooding. The method used in the implementation of this social service program is active participation and mentoring which is carried out gradually and periodically to groups of aquaculturist in Jeruksari Village, Pekalongan Regency. The results of this program show that all service activities starting from counseling sessions, mentoring (shopping materials and making cages), to monitoring when the cultivation period goes very smoothly and the aquaculturist partner groups are also quite enthusiastic about participating. The floating cages made from this program are made from cheap and easily available materials in the surrounding environment, such as bamboo, fishing nets, used floating cans, ropes, and stone weights. Based on the implementation of this program, it can be said that the fish farming community in Jeruksari Village is actually able to create practical examples of floating cage models that can be used as a pond for fish cultivation in areas prone to flooding and tidal flooding.Keywords : fish cultivation, cage, model, mentoring, counseling.